Co-regulation in protecting personal data: The role of industry associations as potential self-regulatory organizations - Ajisatria Suleiman; Pingkan Audrine; Thomas Dewaranu (Center for Indonesian Policy Studies (CIPS), 2022)
As the digital economy is growing in Indonesia at an exponential rate, there is a need to come up with a novel approach to regulating the activities and transactions happening in this space. This is especially true in the sphere of personal data protection, where massive amounts of personal data are collected, processed, and stored by various entities for various purposes. It is difficult for regulators to supervise all activities and ensure compliance with best practices within digital platforms, both in the public and private sector. A co-regulatory approach becomes a potential solution to this issue.
Keywords: 330; Datenschutz; Electronic Commerce; Regulierung; Wirtschaftsverband; Indonesien